Complex segmentectomy in the treatment of stage IA non-small-cell lung cancer. (23rd June 2019) - Handa, Yoshinori; Tsutani, Yasuhiro; Mimae, Takahiro; Miyata, Yoshihiro; Okada, Morihito
Abstract: OBJECTIVES: Although segmentectomy for lung cancer has been widely accepted, complex segmentectomy, which creates several, intricate intersegmental planes, remains controversial. Potential arguments include risk of incurability and 'failure of cancer control'. We compared the outcomes of complex segmentectomy versus lobectomy and evaluated its use in lung cancer treatment. METHODS: We retrospectively reviewed clinical stage IA lung cancer patients who underwent complex segmentectomy ( n = 99) or location-adjusted lobectomy ( n = 94) between April 2009 and December 2017. Clinicopathological and postoperative results were compared. Factors affecting survival were assessed by the Kaplan–Meier method and the Cox regression analysis. RESULTS: No significant differences were detected in 30-day mortality (0% vs 0%), overall complications (26.3% vs 21.3%) and prolonged air leakage (11.1% vs 9.6%) rates between the 2 groups, respectively. Comparable results were obtained for 5-year overall (93.5% vs 96.4%, respectively; P = 0.21) or recurrence-free (92.3% vs 88.5%, respectively; P = 0.82) survivals after complex segmentectomy or lobectomy. There were 2 (2.0%) recurrences after complex segmentectomy and 7 (7.5%) after lobectomy ( P = 0.094), with 0 (0%) margin relapses in each group. Multivariable Cox regression analysis revealed that complex segmentectomy and lobectomy had a numerically similar impact on recurrence-free survival (hazard ratio 0.93, 95% confidence interval 0.32–2.69; P = 0.90). CONCLUSIONS: Complex segmentectomy can provide acceptable short- and long-term outcomes in lung cancer treatment.